2006
DOI: 10.1002/anie.200502540
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of the Electrochemical Activation of Water over Pd by First Principles

Abstract: Structural changes that occur at the palladium(111)/water interface during the electrocatalytic oxidation and reduction of water (see picture) have been calculated by ab initio methods. These results have been used to construct an electrochemical phase diagram, and demonstrate the influence of the polarization of the water/metal interface on surface properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
345
0
3

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 388 publications
(367 citation statements)
references
References 6 publications
4
345
0
3
Order By: Relevance
“…103 Carbon-supported Pd-rich pseudo-core-shell Pd-Pt (Pd@Pt/C) nanoparticles can be prepared by a galvanic replacement reaction, and analyzed using microstructural characterization techniques. 104 Core-shell Pd 70 @Pt 30 catalysts with a loading of 20.4 mg (total metals) per cm 2 showed a minimum two-fold enhancement in their ORR activity in 0.1 M HClO 4 , and presented some advantages in terms of cost and methanol tolerance.…”
Section: Effects Of the Synthetic Methodsmentioning
confidence: 99%
“…103 Carbon-supported Pd-rich pseudo-core-shell Pd-Pt (Pd@Pt/C) nanoparticles can be prepared by a galvanic replacement reaction, and analyzed using microstructural characterization techniques. 104 Core-shell Pd 70 @Pt 30 catalysts with a loading of 20.4 mg (total metals) per cm 2 showed a minimum two-fold enhancement in their ORR activity in 0.1 M HClO 4 , and presented some advantages in terms of cost and methanol tolerance.…”
Section: Effects Of the Synthetic Methodsmentioning
confidence: 99%
“…Several methods [5][6][7][8][9][10][11][12][13] have been proposed for correcting quantum chemical calculations to constant electrode potential. The most elegant solution would be to treat electrons in the grand canonical ensemble, that is, to allow the number of electrons to change during the electronic structure self-consistency loop, which is equivalent to connecting the system to a fictitious potentiostat.…”
Section: Introductionmentioning
confidence: 99%
“…Recent work, however, indicates that such conventions are emerging. 1,2,[6][7][8] It has, for example, been shown that many of the conventions from heterogeneous catalysis and gas-phase reactions can be applied to electrochemistry. 2 This requires a reference to connect the gas-phase surface calculations to those under electrochemical control.…”
Section: Introductionmentioning
confidence: 99%
“…1,6,10 The work function is therefore related to the normal hydrogen electrode, similar to eq 1, via the following equation…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation